Determining sources of groundwater salinity in the multi-layered aquifer system of the bengal delta, Bangladesh (BRAC University Journal, 2026)
The study area lies on the coastal belt of the Bengal Delta, southern Bangladesh. This study bas been condocted to deteonine salinity sources in the multi-layered aquifers of the Bengal Delta. Dissolved major ions including chloride (Cr) and brontide (Br) were measured in groundwater of the coastal areas of Bangladesh to assess the source(s) of salinity. Ionic concentrations of 48 groundwater samples were analyzed for this study; samples were collected from observation wells installed at different depths down to 336 m. The major ion trends of the upper (<200 m deep) Sodium (Na')-Chloride (Cr) groundwater type is defined as Na+> Calcium (Ca2l> Magnesium (Mg'"')> Potassium (K"') and Cl> Bi-carbonate (HC03 )> Sulfate (So,'-). The deep groundwater (201-336 m deep) bas ionic trend of Na+>Ca2+>Mg'+>K+ and HC03>Cl>So.'·. The shallow groundwater (<200 m deep) of the south central coast bas Br:Cr ratios between 0.00234 and 0.00354 and correspondiog Cr:Br molar ratios between 635.51 and 959.78, which indicates that seawater from the ocean is the principal source of chloride in the upper aquifers with the mixture of fresh water mainly recharged from monsoon rain. At some locations in the south-central coast, seawater is also the principal source of the salinity in deep groundwater, within the depth ranging from 201 to 336 m. Elevated chloride concentration might be due to the entrapment of relict seawater in the sediment during Holocene transgression.